2009
DOI: 10.1080/02640410903062019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of technology on sporting performance in Olympic sports

Abstract: To assess the effect of technology on sport, the performance statistics for four disciplines were analysed: the 100-m sprint, pole vault, javelin, and cycling. The concept of a performance improvement index was developed to allow comparison between athletes and between sports with a higher index indicating a greater improvement in the sport. The following performance improvement indices were found: 100-m sprint, 24% over 108 years; pole vault, 86% over 94 years; javelin, 95% over 76 years; 4-km individual purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 10 publications
2
66
0
9
Order By: Relevance
“…The specific reason for this peak can only be speculated. It has been demonstrated that of a typical historical performance improvement change, some of this can be attributed to clothing [8] or the social impact of war [10], but the able-bodied athlete's data over the same evaluated time period do not reflect similar sudden increases in PII that the amputee sprinting group demonstrated. Acknowledging that there were no changes in disability classification at the Paralympics between 1984 and 1988 (which may account for the sudden change in performance or participation), this suggests that there are other causative factors involved which are unique to disability sprinting.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The specific reason for this peak can only be speculated. It has been demonstrated that of a typical historical performance improvement change, some of this can be attributed to clothing [8] or the social impact of war [10], but the able-bodied athlete's data over the same evaluated time period do not reflect similar sudden increases in PII that the amputee sprinting group demonstrated. Acknowledging that there were no changes in disability classification at the Paralympics between 1984 and 1988 (which may account for the sudden change in performance or participation), this suggests that there are other causative factors involved which are unique to disability sprinting.…”
Section: Discussionmentioning
confidence: 97%
“…The PII has also been used to explore the impact of World Wars 1 and 2 upon running short, middle and long distance world records [9], and on the impact of technological innovation in Olympic field jumping events [10]. The PII cannot currently identify the exact proportion of impact of sports technology change, but it has been shown to corroborate anecdotal evidence of change such as the inception of new materials used for the pole vault or a change in the aerodynamic design of bicycles [8]. As a result, it is a complementary tool to inform debate rather than to generate substantive findings.…”
Section: Performance Datamentioning
confidence: 99%
See 3 more Smart Citations